The oscillatory entrainment of virtual pitch perception - Aksentijevic, Aleksandar; Northeast, Anthony; Elliott, Mark (Frontiers in Psychology, 2013)
Evidence suggests that synchronized brain oscillations in the low gamma range (around 33 Hz) are involved in the perceptual integration of harmonic complex tones. This process involves the binding of harmonic components into “harmonic templates” – neural structures responsible for pitch coding in the brain. We investigated the hypothesis that oscillatory harmonic binding promotes a change in pitch perception style from spectral (frequency) to virtual (relational). Using oscillatory priming we asked 24 participants to judge as rapidly as possible, the direction of an ambiguous target with ascending spectral and descending virtual contour. They made significantly more virtual responses when primed at 29, 31 and 33 Hz and when the first target tone was harmonically related to the prime, suggesting that neural synchronization in the low gamma range could facilitate a shift towards virtual pitch processing.